2014
DOI: 10.1039/c4cc01584c
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive robust polymer micelles with metal–ligand coordinated core cross-links

Abstract: We report on pH-responsive core-shell polymer micelles with catechol-Fe(3+) coordinated core cross-links, which provide robustness to drug-loaded polymer micelles and allow the facilitated intracellular release of loaded anticancer drugs in response to an endosomal acidic pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…[38,39] Given that the Fe-ZDS complex was formed by ironcatechol coordination,w ep roposed thatt he complex might exhibit pH-sensitive relaxivities. This uniquef eature has previously been utilized for the construction of nanocarriersw ithp H-triggered drug-releasec apacities.…”
Section: Ph-responsive Longitudinal Relaxivity Of Fe-zdsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38,39] Given that the Fe-ZDS complex was formed by ironcatechol coordination,w ep roposed thatt he complex might exhibit pH-sensitive relaxivities. This uniquef eature has previously been utilized for the construction of nanocarriersw ithp H-triggered drug-releasec apacities.…”
Section: Ph-responsive Longitudinal Relaxivity Of Fe-zdsmentioning
confidence: 99%
“…This uniquef eature has previously been utilized for the construction of nanocarriersw ithp H-triggered drug-releasec apacities. [38,39] Given that the Fe-ZDS complex was formed by ironcatechol coordination,w ep roposed thatt he complex might exhibit pH-sensitive relaxivities. Once the iron complex transformed from saturated tris-coordinationi nto bis-or mono-coordination in the acidic environment, water molecules can directly coordinate with the iron core, which contributes significantly to the r 1 relaxivity of the complex.…”
Section: Ph-responsive Longitudinal Relaxivity Of Fe-zdsmentioning
confidence: 99%
“…At pH 5, the catechol‐Fe 3+ will be partially broken and the anticancer drug will be released. A cumulative release of ~60% DOX was obtained in a period of 24 h (Figure ).…”
Section: Stimuli‐responsive Polyester Nanocarriersmentioning
confidence: 99%
“…In 2014, Gyu Ha Hwang et al [26] reported the synthesis of pH-responsive core-shell polymer micelles through the self-assembly of poly(ethylene glycol)(PEG)-b-poly(L-3,4-dihydroxyphenylalanine) (PEG-b-PDOPA). The amphiphilic block copolymer was synthesized by the ROP of di-O,O'-acetyl-L-DOPA-N-carboxyanhydride ((AC2)-DOPA-NCA) with CH 3 O-PEG-NH 2 as the macroinitiator, followed by deprotection of the hydroxyl groups.…”
Section: Ph-responsive Micellesmentioning
confidence: 99%